A blast from the past: To tame time with metformin. (December 2022) - Xenos, Dionysios; Mecocci, Patrizia; Boccardi, Virginia
Abstract: The strong evidence of metformin use in subjects affected by type 2 diabetes (T2DM) on health outcomes, together with data from pre-clinical studies, has led the gerontological research to study the therapeutic potential of such a drug as a slow-aging strategy. However, despite clinical use for over fifty years as an anti-diabetic drug, the mechanisms of action beyond glycemic control remain unclear. In this review, we have deeply examined the literature, doing a narrative review from the metformin story, through mechanisms of action to slow down aging potential, from lower organisms to humans. Based on the available evidence, we conclude that metformin, as shown in lower organisms and mice, may be effective in humans' longevity. A complete analysis and follow-up of ongoing clinical trials may provide more definitive answers as to whether metformin should be promoted beyond its use to treat T2DM as a drug that enhances both healthspan and lifespan. Highlights: Pre-clinical studies have provided robust evidence on the hypothesis that metformin may slow the aging process. Metformin's mechanisms of action beyond glycemic control remain still unclear. Data from pre-clinical studies are encouraging. Clinical trials may provide more answers as to whether metformin can be used to promote longevity.